Evaluation of Clinical Effects and Tolerability of Cefepime in Hospital Settings in Bangladesh - Islam, Mohammad Manirul; Rahman, ABM Fazlur; Das, Bidhan C; Hossain, Mohammad Zaid; Pervin, Kumkum (Journal of Dhaka Medical College, 2018)
Background: Cefepime a parenteral fourth generation cephalosporin is active against many Gram-positive and Gram-negative organisms. The study aimed to evaluate the effectiveness and tolerability of cefepime when used alone or in combination with other antibiotics for the treatment of infections in hospital settings in Bangladesh. Methods: This multi-centric, prospective observational study enrolled eligible males and females >18 years who had been prescribe cefepime as a part of treatment strategy regardless of the purpose of hospitalization. No therapeutic intervention was implied rather treatment strategy and dosage of cefepime was on individual physician’s discretion as per routine clinical practice. Percentage of patients who would have clinical success in terms of cure, improvement or failure was evaluated during the end of cefepime therapy. Patient’s overall tolerability to cefepime therapy as excellent, good, satisfactory and poor was considered for safety assessment. The outcome analysis was done in patients’ available follow-up at the end of therapy. Results: A total of 1000 patients were enrolled in this study between March 2013 and September 2014 in different hospital settings of Internal Medicine, Coronary Care Unit, Orthopedic, Intensive Care Unit, Surgery and Nephrology (51.6%, 17.8%, 15.2%, 11.6%, 2.2% & 1.6%). The mean (±SD) age of patients was 50.1 (±14.7) years (range 18-100) and 64.3% were males. Bacteriology or culture sensitivity report was available with 67 patients at baseline and most common microorganisms were E coli (35.8%), Pseudomonas sp. (20.8%), Klebsiella sp. (16.4%), Staphylococcus sp. (11.9%) and Streptococcus sp. (7.4%) and others (7.4). Cefepime was used as medical or surgical prophylaxis in 52.2% of the patients. In 47.8% of patients cefepime was prescribed for treatment of infections including lower respiratory tract infections, trauma / fracture related wound infections, urinary tract infections, treatment of gangrene and septicaemia (39.7%, 31.8%, 10.9%, 9.2% & 8.4%). The dose of cefepime was 500 mg to 2 gm twice or thrice daily with the mean (±SD) duration of 6.1 (±2.1) days (range 2-14). 55 patients were lost to follow-up at the end of therapy and 25 died due to congestive heart failure, renal or hepatic failure and multiple organ failure. On physicians end of therapy overall clinical outcome evaluation, 70.7% of the patients were cured, 24.9% improved and 4.4% had no improvement or worsening in the sign and symptoms. Overall tolerability of cefepime was good in 56.6 %, excellent in 28.7%, satisfactory in 9.8% and poor in 4.9% of patients. No non-serious adverse event was reported in this study. Nonetheless, the 25 death cases would be considered as serious adverse events. Conclusion: Cefepime therapy in different indications was effective in hospitalized patients for cure (67.5 %) or improvement (26.9 %) of sign and symptoms. It was also well tolerated in 85.3% of patients as assessed by the treating physicians J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 17-24